(untitled) (Research, Society and Development, 2022)
This article presents some results of a research aimed to analyse the reflective writing of preservice mathematics teachers and identifying the types of reflective writing. For the collection of these writings, an instrument called Caderno de aula com Reflexões (class notebook with reflections), in the context of a discipline of Practice and Methodology of Teaching Mathematics of the Mathematics Degree at a Public University of Paraná. For the analyses, the reading of all the available material was carried out initially, followed by a vertical reading and a horizontal reading of the productions. In general, through the reflective writing of future teachers, it can be noted that they report learning, doubts, clarifications, facts that aroused their interest, study experiences, among other things. Regarding the types of reflexive writings, Explanation Type and Exploration Type writings were identified. It is hoped that the results of this investigation can support other investigations and for the training process of other teachers.